Manipulasi Laporan Keuangan Konsolidasi dalam Entitas Konsolidasi: Studi Kasus PT Envy Technologies Indonesia Tbk - Agape Anjumarito Panjaitan; Merlindang Simamora; Sarah Agustin Siahaan; Putri Wulandari Nasution; Jose Andrian Simbolon; Tapi Rumondang Sari Siregar (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Manipulation of financial statements in consolidated entities is one of the serious problems in the business world and capital markets. The case of PT Envy Technologies Indonesia Tbk is a clear example of how companies can manipulate financial statements to provide a better picture to investors and stakeholders. This study aims to identify manipulation techniques used in consolidated financial statements, analyze their impact on investors and the capital market, and evaluate the effectiveness of Indonesian regulations in dealing with these practices.This research uses the literature study method by analyzing various academic journals, company financial statements, and related regulations applicable in Indonesia. The results show that manipulation techniques that are often used include overstatement of revenue, recording of fictitious transactions, and concealment of liabilities. The impact is very significant, including investor losses due to erroneous investment decisions, falling stock prices, and loss of market confidence in the company and existing regulations.In addition, the study found that although regulations in Indonesia, such as those overseen by the Financial Services Authority (OJK) and the Indonesia Stock Exchange (IDX), have been implemented, there are still loopholes that allow for manipulation of financial statements before they come to light. Therefore, strengthening the supervision and audit system, increasing transparency in the presentation of financial statements, as well as stricter sanctions against violations are needed to prevent similar cases from occurring in the future.